A comparison of thermally conductive polyamide 6‐boron nitride composites produced via additive layer manufacturing and compression molding. Issue 6 (6th March 2021) - Bragaglia, Mario; Lamastra, Francesca R.; Russo, Pietro; Vitiello, Libera; Rinaldi, Marianna; Fabbrocino, Francesco; Nanni, Francesca
Abstract: Thermally conductive but electrically insulating polymer matrix composites are of great interest in many engineering applications such as thermal management applications (i.e., heat sinks in microelectronic packaging, cooling of mechatronic components and mechanisms). Among possible functional fillers, hexagonal boron nitride seems to be one of the most promising choice due to its high thermal conductivity, and in this work, it was used as filler of polyamide 6 matrix. The resulting composites were first prepared in the form of pellets, extruded into filaments, and successively 3D printed, with the aim to study and compare the thermal performances of the 3D printed samples to the ones manufactured using traditional compression molding technique. The thermal conductivity of 25% wt and 45% wt loaded compression molded samples were 1 and 2.5 W/mK, respectively, while the neat polymer showed a thermal conductivity of 0.29 W/mK. 3D printed samples showed the same trend, namely increasing thermal conductivity with filler amount, despite a great influence of the 3D printing processing parameters (i.e., melt rheology and printing temperature), which lower the resulting thermal conductivity. 3D printed 25% and 45% by weight loaded samples showed a through plane thermal conductivity of 0.67 and 0.92 W/mK, respectively, and in‐plane thermal conductivity of 0.96 and 1.52 W/mK due to the presence of porosity and filler alignment along the printing direction. Abstract : PA6‐BN composites were 3D printed. The thermal conductivity of 25% wt and 45% wt loaded 3D printed samples increased with filler amount despite a great influence of the 3D printing processing parameters (i.e., melt rheology and printing temperature).